Studi Kajian Ilmu Sosial sebagai Upaya Meningkatkan Pemahaman Multikultural Siswa Jurusan IPS MAN 2 Kota Kediri - Ridwanulloh, M. Ubaidillah; Parawansa, Fitriani Chofifah (IAIN Madura, 2023)
The purpose of this research is to describe the school's strategy for teaching social studies subjects through Social Studies Studies (SKIS). Multicultural Education is an effort to integrate into one multicultural understanding of the many diversity in Indonesia. An education based on instilling multicultural values will help students in each school understand the richness of culture and appreciate differences in every respect, starting from differences in ethnicity, religion, race, ethnicity, and so on. This research method uses a descriptive qualitative method. Sources of data obtained from observation, interview, and, documentation. The informants in this study were the deputy head of the curriculum, the social studies teacher, and several students majoring in social studies. The results of the study show that the multicultural education strategy is carried out not only through social studies subjects but also using the Social Science Study Study (SKIS) strategy. Implementation of the SKIS method by visiting several historical tourist attractions related to social studies including the Trowulan Mojokerto Temple, an area of the Hindu community in Banyuwangi, along with historical sites that contain culture. The influence of SKIS activities makes students happy and able to understand directly based on experience with objects of the nation's cultures.